Underground coal gasification – Part I: Field demonstrations and process performance. (July 2018) - Perkins, Greg
Abstract: Underground coal gasification can convert deep coal resources into synthesis gas for use in the production of electricity, fuels and chemicals. This paper provides a review of the various methods of undertaking underground coal gasification and observations from demonstrations of the process in the field. A general representation of the underground process is presented, along with an identification of the various zones and associated governing phenomena. The main factors affecting the performance of underground coal gasification, such as coal rank, depth and thickness and oxidant composition and injection rate are examined in detail. A brief assessment of the economic and environmental considerations relevant to underground coal gasification projects is presented. Finally, guidelines for site and oxidant selection are provided based on the learnings from prior demonstration projects.